Cross country : [large type] : a novel - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2008)
Believing he is investigating the work of a horrible new breed of killer when he encounters a murder scene of particular violence at the home of his oldest friend, detective Alex Cross finds himself entangled in the deadly Nigerian underworld of Washington, D.C.